(3eQhjGJ CejQ GdeDefjf GdYHGSs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO aeGRGdJ GdNdaGA CQHGH GdQJHI GdefjaI djLeYhG Hjf GdNdGaJjf NdGaI GdQYGjI hNdGaI GdQhGjI s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde ddYHGS QVi Gddg Yfg EPG cGf ZOGg GdCKfjf aCJfj CfJ hhdOc MJi COYh dge HOYhg jfaYc Gddg hhdOc Ke bGd Gddge ZaQ ddYHGS hhdOg eZaQI XGgQI hHGWfg dGJZGOQ PfHkG Gddge CMaXg aj hdOg s
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027 (3c(B) s
Keywords: (3GdMOjK h GdeUWdMs